Manejo de la encefalopatía por kernicterus en el recién nacido - Chicaiza Montero, Joel Francisco (2023)
ABSTRACT: Hyperbilirubinemia is a condition that can occur in up to 80% of newborns. Generally its evolution is favourable; however, in some cases the levels of bilirubin in the blood increase severely and cause a disease called kernicterus encephalopathy. Its presence increases the risk of serious complications, irreversible sequelae and even the death of the patient. Clinical suspicion, early diagnosis and adequate treatment are the fundamental elements of managing this condition. The objective of this research was to update the scientific information on the most adequate management of kernicterus encephalopathy in newborns. For this, a basic, descriptive and cross-sectional investigation was carried out consisting of a bibliographic review of documents published in the last 5 years. 42 documents were identified that were used in the study. The information was obtained from regional (Latindex, Lilacs, Scielo, and Redalyc) and high-impact databases (Scopus, Medline, PubMed, and Ice Web of Science). The main results include the description of the clinical manifestations, causes, etiopathogenic mechanisms and complications of the disease. It is concluded that despite the fact that kernicterus encephalopathy is not a frequent disease, considering the complications it generates, it is necessary to maintain a permanent update on the clinical, diagnostic and therapeutic characteristics of the disease. Keywords: Newborn; hyperbilirubinemia; Kernicterus; Clinical management